[N,N'-Bis(3-Aminopropyl)Ethylenediamine]Disaccharinatozinc(II) Monohydrate - Paaolu, H.; Kaştaş, G.; Yeşilel, O.Z.; Sahin, O.; Büyuk̈güngör, O. (Blackwell Publishing, 2007)
In the title complex, [Zn(C7H4NO3S)2(C8H22N4)]·H2O or [Zn(sac)2(paen)]·H2O [sac = saccharinate and paen = N,N′-bis-(3- amino-prop-yl)ethyl-enediamine], the zinc cation is octa-hedrally coordinated. The equatorial plane of the octa-hedron is formed by N atoms of the paen ligand, whereas the axial positions are occupied by the carbonyl O atoms of the two sac ligands. One of the sulfonyl groups of the sac ligands shows disorder and was modelled with two different orientations and site occupancies of 0:38 (1):0.62 (1). The mol-ecular packing is stabilized by inter-molecular O - H⋯O and N - H⋯O hydrogen bonds between water mol-ecules and neighbouring [Zn(sac)2(paen)] mol-ecules, which form chains running parallel to [010]. The crystal used was an inversion twin. © International Union of Crystallography 2007.